Anatomical Resections Improve Survival Following Lung Metastasectomy of Colorectal Cancer Harboring KRAS Mutations. Issue 6 (December 2019) - Renaud, Stéphane; Seitlinger, Joseph; Lawati, Yaseen Al; Guerrera, Francesco; Falcoz, Pierre-Emmanuel; Massard, Gilbert; Ferri, Lorenzo; Spicer, Jonathan
Abstract : Objective: The aim of this study was to evaluate the benefit of anatomical resection (AR) in lung metastasectomy (LM) of colorectal cancer (CRC) harboring KRAS mutations Summary Background Data: KRAS mutations are related to high aggressiveness in the lung metastasis of CRC. It is unknown whether AR can lead to better outcomes than can non-AR (NAR) in KRAS patients. Methods: We retrospectively reviewed the data from 574 consecutive patients who underwent a LM for CRC. We focused on patients exhibiting 1 lung metastasis who underwent an AR (segmentectomy) or an NAR (wedge) and for whom the KRAS mutational status was known. Overall survival (OS) and time to pulmonary recurrence (TTPR) were analyzed. Results: We included 168 patients, of whom 95 (56.5%) harbored KRAS mutations. An AR was performed in 74 patients (44%). The type of resection did not impact the median OS in wild-type (WT) patients ( P = 0.67) but was significantly better following AR in KRAS patients (101 vs 45 months, P = 0.02) according to the multivariate analysis [hazard ratio (HR): 6.524; 95% confidence interval (CI), 2.312–18.405; P < 0.0001). TTPR was not affected by the type of resection in WT patients ( P = 0.32) but was significantly better for AR in KRAS patients (50 vs 15 months, P = 0.01) in the multivariate analysis (HR: 5.273; 95% CI, 1.731–16.064; P = 0.003). The resection-margin recurrence rate was significantly higher for NAR in KRAS patients (4.8% vs 54.2%, P = 0.001) but not in WT patients (P = 0.97). Conclusion: AR seems to improve both the OS and TTPR in LM of CRC harboring KRAS mutations.